The Impact Assessment of Entrepreneurship and Innovation on Job Creation and Economic Development in the Mekong Delta Region - Pham , Ánh Nguyệt (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study assesses the impact of entrepreneurship and innovation on job creation and economic development in the Mekong Delta region. Data were collected from 380 startup enterprises through a quantitative survey, supplemented by qualitative analysis from expert interviews. Statistical methods such as Cronbach’s Alpha, Confirmatory Factor Analysis (CFA), and multiple linear regression were employed to test the research hypotheses. The results indicate that: (1) Entrepreneurship has a positive impact on job creation and economic growth; (2) Innovation plays a crucial role in enhancing labor productivity and competitiveness; (3) The combination of entrepreneurship and innovation generates a synergistic effect, optimizing economic impact; (4) Observational variables significantly influence the relationship between entrepreneurship, innovation, and economic development. Based on these findings, several managerial implications are proposed to foster a conducive environment for entrepreneurship and innovation in the Mekong Delta region. These include enhancing managerial capabilities, improving access to finance, developing high-quality human resources, and strengthening policy support.